A Systematic Review of Primary, Adjuvant, and Salvage Radiation Therapy for Cutaneous Squamous Cell Carcinoma. Issue 5 (11th May 2021) - Krausz, Aimee E.; Ji-Xu, Antonio; Smile, Timothy; Koyfman, Shlomo; Schmults, Chrysalyne D.; Ruiz, Emily S.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : BACKGROUND: The gold standard of treatment for cutaneous squamous cell carcinoma (cSCC) is surgery radiation therapy (RT) is used selectively as definitive treatment for low-risk tumors or as adjuvant/salvage treatment for high-risk tumors. There is a lack of standardized studies evaluating the efficacy of RT in either clinical scenario. OBJECTIVE: To determine the efficacy of primary and adjuvant/salvage RT for the treatment of cSCC. MATERIALS AND METHODS: A systematic review of PubMed, Embase, Cochrane, and Web of Science was performed for studies that reported outcomes of cSCC treated with RT to the primary site alone. Outcomes included local control (LC), local recurrence (LR), nodal metastases (NM), distant metastases (DM), disease-specific death (DSD), and recurrence-free survival (RFS). RESULTS: Forty-six studies with 4, 141 tumors were included. Pooled LC and LR rates were 87.3% and 8.6%, respectively. The rates of NM, DM, DSD, and RFS were 4.8%, 3.5%, 5.3%, and 73.5%, respectively. Local recurrence was significantly higher for T3 and T4 tumors, with rates above 25.9%. CONCLUSION: LR after RT to the primary site increased with increasing tumor stage, highlighting the importance of clear surgical margins for high-risk tumors. Prospective randomized studies characterizing outcomes by tumor stage for RT compared with surgery are needed to inform guidelines.